Craniofacial injuries in Brazilian women victims of aggression - Cárdenas, Liz Lider Maggi; Ribeiro, Isabella Lima Arrais; Barbosa, Gabrielle Stella Dantas; Castro, Ricardo Dias de; Genú, Paloma Rodrigues (ARCHIVES OF HEALTH INVESTIGATION, 2017)
Objective: To characterize craniofacial injuries in Brazilian women who were victims of violence in 2005 and 2015. Methods: Descriptive and retrospective study with data collected from records of victims with craniofacial injuries from the forensic medicine institute of a Brazilian city with a large population. The following information was recorded: age, civil status, degree of aggressor kinship, location of the injury and type of instrument used in the aggression. The data were analysed using IBM SPSS (21.0), and a 5% significance level was adopted. Main results: A total of 962 records were assessed, including 481 from 2005 and 481 from 2015. When 2005 and 2015 were compared, an increase in the number of records of victims in the age range 31 years and above was found, with the largest number of records related to victims 51 to 60 years old (38.48%). The intraoral region and hard tissues were significantly more affected in 2015 than in 2005 (p<0.001). Conclusions: No changes in the numbers of aggression victims were observed between 2005 and 2015. After the approval of the Maria da Penha Law, aggression were focused more on age ranges older than 31 years. The number of aggression perpetrated by first-degree relatives was greater in 2015 than in 2005, as was the number of injuries to the intraoral region and hard tissues. Descriptors: Violence Against Women; Wounds and Injuries; Forensic Medicine; Domestic Violence.